An Experimental Rat Model of C5 Palsy Following Posterior Decompression Surgery of the Cervical Spine. Issue 3 (11th August 2021) - Yokota, Atsushi; Fujishiro, Takashi; Usami, Yoshitada; Neo, Masashi
Abstract : To clarify the structural and functional alterations of cervical roots following posterior decompression, a rat model of cervical laminectomy was developed, and in vivo analyses were performed up to 14 days postoperatively. Tethering of the anterior rootlets due to posterior cord shift was considered a possible mechanism causing delayed paresis. Abstract : Study Design: Basic in vivo research. Objectives: The aim of this study was to establish an animal model that is appropriate for analyzing the mechanisms of C5 palsy (C5P) and to clarify the structural and functional alterations of cervical roots following posterior decompression. Summary of Background Data: Although C5P is one of the major complications of cervical surgery, the exact pathogenesis of C5P remains unclear partly because of the lack of an appropriate animal model. Tethering of the cervical roots due to posterior cord shift following posterior decompression is thought to be one of the possible factors that cause C5P. Methods: Twenty-eight Sprague-Dawley rats were divided into Group L (cervical laminectomy, N = 18) or Group S (sham surgery, N = 10) and examined up to postoperative day 14 (PO14). Posterior cord shift and the length of the anterior rootlets were quantified by computed tomography-myelogram images. Motor evoked potential (MEP) of the deltoid (C5, 6 innervated) and triceps brachii (C7-T1 innervated), mechanical allodynia, and grip strength of the forepaw (C7-T1 regulated) were measured. Results: All anterior rootlets were elongated as the cord gradually shifted posteriorly postoperatively. The elongation rate of the C6 anterior rootlets was the highest (142% at PO14). The MEP latency of the deltoid was significantly delayed throughout all postoperative time points. However, significant delay in the latency of the triceps brachii was observed only on postoperative day 10. The withdrawal threshold of the forepaw did not change; grip strength of the forelimb decreased at PO14. Conclusion: This model was thought to be appropriate for analyzing the pathogenesis of C5P since our findings were comparable to the clinical course of C5P subsequent to posterior cervical decompression. Although a future study for clarifying histological and molecular alterations will be needed, tethering of the anterior rootlets due to posterior cord shift was suggested to be a probable mechanism causing C5P. Level of Evidence: 5